2004
DOI: 10.1177/0272989x04271329
|View full text |Cite
|
Sign up to set email alerts
|

Theory about Heuristic Strategies Based on Verbal Protocol Analysis: The Emperor Needs a Shave

Abstract: A research report in the present issue of Medical Decision Making raises questions about the definition of heuristic strategies, the validity of conclusions drawn from the analysis of verbal protocols, and the tradeoff between rigor and relevance in research on the psychology of patient decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…However, because we did not use ''think-aloud'' protocols or (structured) interviews with the FPs, to avoid interfering with the normal consultation process, our observations alone could not identify the theoretical concepts with which FPs' decisions most closely corresponded. 44 Statistical analyses gave further evidence for a ''simplified'' process. Because there were only a few patients in the sample for whom all of the relevant predictors were identified, using history taking and physical examination, we expected that logistic regression models containing all relevant predictors (saturated model) would be significantly overfitted.…”
Section: Decision Making Regarding Diagnosesmentioning
confidence: 98%
“…However, because we did not use ''think-aloud'' protocols or (structured) interviews with the FPs, to avoid interfering with the normal consultation process, our observations alone could not identify the theoretical concepts with which FPs' decisions most closely corresponded. 44 Statistical analyses gave further evidence for a ''simplified'' process. Because there were only a few patients in the sample for whom all of the relevant predictors were identified, using history taking and physical examination, we expected that logistic regression models containing all relevant predictors (saturated model) would be significantly overfitted.…”
Section: Decision Making Regarding Diagnosesmentioning
confidence: 98%
“…However, in psychology, there is recognition that heuristics are not something to be expunged, but rather exist in part to provide satisfactory solutions to problems consistent with the constraints of human abilities to process information. This position grew out of the concept of ''bounded rationality' that characterized the field of ''heuristics and biases'' in the 1970's (Hamm 2004). In contrast to the dominant view in the diagnostic error literature, studies in psychology have shown that analytical approaches are often inferior to System 1 methods (Wilson and Schooler 1991;Dijksterhuis et al 2006).…”
Section: Dual Processes Errors and Expertisementioning
confidence: 99%
“…A recent commentary observes: 'The broader community of medical decision-making researchers has not embraced the topic of heuristics and biases approach with sustained enthusiasm.' 24 More specifically, failure of the theory of heuristic strategies has been attributed to its weak predictive power, its inability to describe the judgement process in sufficient detail or to explain individual differences, and to its failure to assist physicians in improving their decision-making. 25 Thus, in the hands of those who might be best positioned to develop a robust theory and application of heuristic strategies, the work appears to have stalled.…”
mentioning
confidence: 99%